(3eNJGQ GddaX aj GdWHs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eGfM GdKhGH , haGJM GdCHhGH jfHZiGdBOei Cf jchf ecKg ai ghGA LjO GdLhgQ , dGjNGdWg HNGQ hdGONGf s
(3BNQgG (B:s
(3hba efXQkG eLF GdQSd eJaJkG Yf eMGOKI GdNdb Edi eHGOQI GdPcQ hGdESJZaGQ , hdjfJgH dReGf HQab hdjbGhe Nhag ef GdehJ HMSf dXf ai GdaVd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B221 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQj edj s
Keywords: (3GdWHs